ASSESSING THE IMPACT OF ECONOMIC SERVICES EXPENDITURE ON NIGERIAN ECONOMIC GROWTH: EVIDENCE FROM A NONLINEAR ARDL APPROACH (1981 – 2022) - Bappahyaya, Bashir; Abraham Alexander, Anfofum; Zakaree, Saheed; Imoudu Egwaikhide, Christian; Yakubu, Alfa (African Journal of Social and Behavioural Sciences, 2024)
This study investigates the relationship between economic services expenditure and Nigeria's economic growth from 1981-2022 using a Nonlinear Autoregressive Distributed Lag (NARDL) model. The study aims to find out whether economic services expenditure, particularly in sectors such as agriculture and infrastructure, significantly contributes to economic growth in Nigeria. The findings reveal a significant long-run relationship between government expenditure on agriculture, roads, and construction and economic growth, while transport and communication spending negatively affects growth. Recommendations include increased investment in agriculture and infrastructure to support economic development.